PERAN DIGITAL FINANCIAL LITERACY DALAM MEMODERASI PENGARUH DIGITAL PAYMENTS DAN CASH PAYMENTS TERHADAP SPENDING BEHAVIOR GENERASI MILENIAL - Teguh, Ansella Jovita; Wiranata, Destya; Setiadiwiria, Mahersya Christiani; Pertiwi, Dewi (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
The main objective of this study is to examine the effect of payment systems on spending behavior in the millennial generation in Surabaya, with digital financial literacy as a moderating variable. The research method used is a quantitative method with a causal research type. The data obtained came from respondents’ answers through a questionnaire distributed online using Google Form with 107 respondents. Samples were taken using Purposive Sampling technique. The data analysis technique used is the Structural Equation Modeling (SEM) technique by utilizing the Smart-PLS program. The result of this study indicates that digital payment has a significant effect on spending behavior, where the convenience offered by digital payment can cause excessive spending. Cash payment also has an influence on spending behavior because it is difficult to remember how much spending has been done when using cash. The effect of digital financial literacy as moderating variable on the relationship between digital payments/cash payments and spending behavior is negatively correlated, where DFL does not function effectively as moderation in the relationship between DP/CP dan SB.